Tuesday
March 28, 2017

Post a New Question

Posted by on .

*simplify by combining like terms, if possible. then, remove the GCF and factor fully.

2x^2-21x+36+x^2
=3x^2-21x+36
...i'm not sure what to do after that, could you help and show the steps please

  • math - ,

    3x^2-21x+36 GCF: 3, so divide the whole thing by 3.

    x^2-7x+12
    (What two #s add up to -7 and multiplied equal 12? 3 and 4)

    [x^2-4x] - [3x+12]
    x(x-4) - 3(x-4)
    (x-4)(x-3)=0

    x-4= 4 x-3= 3 Answer X=3 and 4

  • math - ,

    I thought it said, factor fully.

    You had
    3x^2 - 21x + 36 , which is correct
    = 3(x^2 - 7x + 12)
    = 3(x-4)(x-3)

    nothing was said about "solving" the equation, since there was no equation.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question